MtDNA copy number associated with age of onset in familial amyloid polyneuropathy. Issue 3 (10th October 2017) - Santos, Diana; Santos, Maria João; Alves-Ferreira, Miguel; Coelho, Teresa; Sequeiros, Jorge; Alonso, Isabel; Oliveira, Pedro; Sousa, Alda; Lemos, Carolina; Grazina, Manuela
Abstract : Background: Transthyretin-related familial amyloid polyneuropathy (TTR-FAP Val30Met) shows a wide variation in age-at-onset (AO) between generations and genders, as in Portuguese families, where women display a later onset and a larger anticipation (>10 years). Mitochondrial DNA (mtDNA) copy number was assessed to clarify whether it has a modifier effect on AO variability in Portuguese patients. Methods: The mtDNA copy number of 262 samples (175 Val30Met TTR carriers and 87 controls (proven Val30Val)) was quantified by quantitative real-time PCR. Statistical analysis was performed using IBM SPSS V.23 software. Results: This study shows that Val30Met TTR carriers have a significantly higher (p<0.001) mean mtDNA copy number than controls. Furthermore, the highest mtDNA copy number mean was observed in early-onset patients (AO <40 years). Importantly, early-onset offspring showed a significant increase (p=0.002) in the mtDNA copy number, when compared with their late AO parents. Conclusions: The present findings suggest, for the first time, that mtDNA copy number may be associated with earlier events and may therefore be further explored as a potential biomarker for follow-up of TTR-FAP Val30Met carriers.